Examining the use of the NeQuick bottomside and topside parameterizations at high latitudes. Issue 1 (1st January 2018) - Themens, David R.; Jayachandran, P.T.; Varney, Roger H.
Abstract: An examination of the high latitude performance of the bottomside and topside F-layer parameterizations of the NeQuick electron density model is presented using measurements from high latitude ionosonde and Incoherent Scatter Radar (ISR) facilities. For the bottomside, we present a comparison between modeled and measured B2Bot thickness parameter. In this comparison, it is seen that the use of the NeQuick parameterization at high latitudes results in significantly underestimated bottomside thicknesses, regularly exceeding 50%. We show that these errors can be attributed to two main issues in the NeQuick parameterization:(1) through the relationship relating foF2 and M3000F2 to the maximum derivative of F2 electron density, which is used to derive the bottomside thickness, and (2) through a fundamental inability of a constant thickness parameter, semi-Epstein shape function to fit the curvature of the high latitude F-region electron density profile. For the topside, a comparison is undertaken between the NeQuick topside thickness parameterization, using measured and CCIR-modeled ionospheric parameters, and that derived from fitting the NeQuick topside function to Incoherent Scatter Radar-measured topside electron density profiles. Through this comparison, we show that using CCIR-derived foF2 and M3000F2, used in both the NeQuick and IRI, results in significantly underestimated topside thickness during summer periods, overestimated thickness during winter periods, and an overall tendency to underestimate diurnal, seasonal, and solar cycle variability. These issues see no improvement through the use of measured foF2 and M(3000)F2 values. Such measured parameters result in a tendency for the parametrization to produce a declining trend in topside thickness with increasing solar activity, to produce damped seasonal variations, and to produce significantly overestimated topside thickness during winter periods.